Decrease of Bullying Behavior in Children Age School Based on Cognitive Behaviour Therapy - Iswanti, Dwi Indah (Health Notions, 2017)
The violence that occurs in education is known as bullying. Violence can occur in mild degrees such as cheating on exams, to fights or beatings that result in death. Bullying in children often leads to school phobias (ask for school change, reduced learning concentration, decreased learning achievement, and likes to carry certain items). Interventions that can be done include Problem Solving Therapy (PST), Behavior Modification (behavior modification), and Cognitive Behavior Therapy (CBT). The purpose of this study was to produce CBT modules in school-aged children that were useful for reducing bullying behavior, using a pre-post test with control group design. The subject of this research is 52 elementary school age children in Tembalang District Semarang selected by purposive sampling technique. Data were collected using bullying behavior checklist, CBT module and workbook, then analyzed using T-Test. The results showed a decrease in bullying behavior in the intervention group after CBT Individual therapy was given.